Role of the tightly bound quinone for the oxygen reaction of cytochrome bo3 oxidase from Escherichia coli. Issue 20 (19th October 2018) - Melin, Frédéric; Sabuncu, Sinan; Choi, Sylvia K.; Leprince, Agathe; Gennis, Robert B.; Hellwig, Petra
Abstract : The coupling of the reaction of a tightly bound ubiquinone with the reduction of O2 in cytochrome bo 3 of Escherichia coli was investigated. In the absence of the quinone, a strongly diminished rate of electrocatalytic reduction of oxygen is detected, which can be restored by adding quinones. The correlation of previous EPR data with the electrocatalytic study on mutations in the binding site at positions, Q101, D75, F93, H98, I102 and R71 reveal that the stabilization of the radical is not necessary for the oxygen reaction. The Q101 and F93 variants exhibit both well‐defined catalytic i– V curves, whereas D75H, H98F, I102W and R71H exhibit broad i– V curves with large hysteresis pointing toward a strong alteration in their catalytic activity. Abstract :